Percursos formativos no curso normal regional de São Francisco de Paula-RS (1953-1962): histórias e memórias - Daros, Dilnei Abel (My University, 2021)
The thesis is located in the field of History of Education and is linked to the line of research in History and Philosophy of Education, of the Graduate Program in Education at the University of Caxias do Sul - UCS, in Caxias do Sul in Rio Grande do Sul and has as object of study the Regional Normal Course, of the Normal School of the municipality of São Francisco de Paula / RS, between 1953 and 1962. In this sense, the research sought to analyze and understand the process of teacher training in São Francisco Paula, based on memories and representations. The theoretical framework used was that of Cultural History and are problematized concepts that involve time, identity and teacher constitution, teacher training, school culture, representation, practice, and appropriation which lead to the analysis of the training process developed in that period. The thesis is organized into 5 parts with 4 chapters and the final considerations observed after the end of the research. In chapter 1 are the initial considerations and descriptions regarding the methodological use of oral history, memories and documentary sources. In this chapter, the interest in understanding the functioning of a teacher training institution was outlined, in this case, the Regional Normal School of that municipality. The questions about the object of study and the objectives that the research sought to answer are mentioned, as well as the theoretical-conceptual and methodological contributions that accompanied the study. I consider it valuable for this study to use all the documental input (writing, photography, memory) that was mobilized, as they brought contributions to answer the questions that were proposed in the search to understand that training environment. In chapter 2, teacher training in a municipality in the fields above the mountains is described briefly with aspects related to the historical part involving instruction/training in the middle of the 19th century, the importance of the arrival of the CNR in the region to meet the demand existing at the time, description of the historical formation of the municipality, mention of local, social, cultural, political and religious conditions, as well as the installation of the School Group in 1918, a historical record of the first decades with enrollment charts, number of schools and the construction of the building that would host ENR.In chapter 3 is contemplated the Normal School: the Regional Normal Course in São Francisco de Paula (1953-1962) and are described the authorization to install the CNR, the opening, the announcements of the event, the opening of enrollments, political elements, first course teachers, terms of tenure, movements of employees, the composition of the first classes of normalists and their characteristics. The first minutes of meetings with its guidelines and directives are transcribed, as well as the existence of the school's internal institutions. The last chapter involves the formative processes: identities, cultures, and practices along with the categories identified after analyzing the documents and recording of the interviews. The universe that permeated the formative process and its most salient marks is described. Parts of the graduates' narratives are described and corroborate the characteristics of that formative process. It is possible to perceive the constitution of an identity constructed with traits linked to the daily life of elements existing within the CNR, evidencing the educational context with the teacher. The final considerations indicated the importance of the school collection in this study (the need to preserve and institutionalize school archives for studies involving the History of Education and its micro fields) as well as the importance of using memories as a document for teachers (alumni/principals). The use of digital technologies for distance interviews is highlighted, which may constitute a new element in researches involving oral history. Being a normalist at the CNR was to have a life made up of daily processes within the training, where it was intended to forge an identity in the teachers, not meaning that it was nuanced this personality, as each teacher had their strategies and forms of resistance in their practice. A Normal Course that produced a teaching identity in São Francisco de Paula, perceived to the present day, since the institution that completed 100 years during the research still maintains a Teaching Course with more than 65 years. The institution has a recognized social relevance in the region, within a tradition linked to teacher training since the 1950s, evidenced in the narrative speeches of newspapers and graduates. This study maintains the possibility of continuing research in the future with this school institution in relation to other objects of study, as well as different time frames. [resumo fornecido pelo autor]
A tese situa-se no campo da História da Educação e vincula-se à linha de pesquisa de História e Filosofia da Educação, do Programa de Pós-graduação em Educação da Universidade de Caxias do Sul - UCS, em Caxias do Sul no Rio Grande do Sul, e tem como objeto de estudo o Curso Normal Regional, da Escola Normal do município de São Francisco de Paula/RS, entre 1953 e 1962. Nesse sentido, a pesquisa buscou analisar e compreender o processo de formação de professoras de São Francisco de Paula, a partir de memórias e representações. O referencial teórico utilizado foi o da História Cultural e são problematizados conceitos que envolvem tempo, identidade e constituição docente, formação de professores, cultura escolar, representação, prática e apropriação, os quais desembocam na análise do processo formativo desenvolvido naquele período. A tese está organizada em 5 partes sendo 4 os capítulos e mais as considerações finais observadas a partir do término da pesquisa. No capítulo 1 estão as considerações iniciais e as descrições referentes ao uso metodológico da história oral, memórias e fontes documentais. Nesse capítulo delineou- se o interesse em compreender o funcionamento de uma instituição formadora de professores, no caso a Escola Normal Regional daquele município. São mencionadas as indagações sobre o objeto de estudo e os objetivos que a pesquisa buscou responder, bem como os aportes teórico-conceituais e metodológicos que acompanharam o estudo. Considero valioso para esse estudo a utilização de todo o aporte documental (escrito, fotografia, memória) que foi mobilizado, pois trouxeram contribuições para responder aos questionamentos que foram propostos na busca por compreender aquele ambiente de formação. No capítulo 2 a formação de professores em um município dos campos de cima da serra está descrita de maneira sucinta com aspectos ligados à parte histórica envolvendo a instrução/formação na metade do século XIX, a importância da chegada do CNR na região ao atender a demanda existente na época, descrição da formação histórica do município, menções sobre as condições locais, sociais, culturais, políticas, religiosas, assim como a instalação do Grupo Escolar em 1918, registro histórico das primeiras décadas com gráficos de matrículas, número de escolas e a construção do prédio que iria sediar a ENR. No capítulo 3 está contemplada a Escola Normal: o Curso Normal Regional em São Francisco de Paula (1953-1962) e descreve-se a autorização de instalação do CNR, a abertura, os anúncios do evento, abertura de matrículas, elementos políticos, primeiros professores do curso, os termos de posse, movimentações de funcionários, composição das primeiras turmas de normalistas e suas características. São transcritas as primeiras atas de reuniões com suas orientações e diretrizes, bem como a existência das instituições internas da escola. O último capítulo envolve os processos formativos: identidades, culturas e práticas, juntamente com as categorias identificadas após análise dos documentos e degravação das entrevistas. É descrito o universo que permeou o processo formativo e suas marcas mais salientes. Partes de narrativas das egressas são descritas e corroboram características daquele processo formativo. Percebe-se a constituição de uma identidade construída com traços ligados ao cotidiano de elementos existentes dentro do CNR, evidenciando o contexto educacional com o docente. As considerações finais indicaram a importância do acervo escolar nesse estudo (necessidade de preservação e institucionalização dos arquivos escolares para os estudos envolvendo a História da Educação e seus micros campos), bem como a importância do uso das memórias como documento das professoras (egressas/ diretoras). Destaca-se o uso das tecnologias digitais para as entrevistas à distância, o que pode constituir um elemento novo nas pesquisas que envolvam a história oral. Ser normalista no CNR era ter uma vida constituída de processos diários dentro da formação, onde se pretendeu forjar uma identidade nos professores, não significando que matizou essa personalidade, pois cada docente possuía suas estratégias e formas de resistência em sua prática. Um Curso Normal que produziu uma identidade docente em São Francisco de Paula, percebida até os dias atuais, tendo em vista que a instituição que completou 100 anos durante a pesquisa ainda mantém um curso de Magistério com mais de 65 anos. A instituição possui relevância social reconhecida na região, dentro de uma tradição ligada à formação de professores desde a década de 1950, evidenciada nos discursos narrativos dos jornais e das egressas. Esse estudo mantém a possibilidade de continuação de pesquisas no futuro, junto a essa Instituição escolar em relação com outros objetos de estudo, bem como recortes temporais distintos.[resumo fornecido pelo autor]
Keywords: Educação - História - São Francisco de Paula, RS; Professores - Formação - São Francisco de Paula, RS; Education - History - São Francisco de Paula, Brazil; Teachers, Training of - São Francisco de Paula, Brazil